Mitigating Workplace Accident Risks through Job Safety Analysis (JSA) in the Reconstruction of Post-Earthquake Buildings in Cianjur Regency - Christian, Johan (Science and Technology Research Centre, Universitas PGRI Semarang, 2025)
The reconstruction of buildings post-earthquake presents significant challenges, particularly in ensuring the safety of construction workers. This study focuses on the application of Job Safety Analysis (JSA) to mitigate workplace accident risks in the reconstruction of buildings in Cianjur Regency, Indonesia, following a major earthquake. By systematically identifying hazards and implementing control measures, JSA aims to improve safety outcomes and support successful project completion. This paper presents a comprehensive analysis of JSA methods, their application in the context of earthquake reconstruction, and their effectiveness in reducing workplace accidents.Keywords: JSA, risk, mitigation